Spin correlations in tt[bar] events from pp collisions : measured at √s = 7 TeV in the lepton+jets final state with the ATLAS detector /: measured at √s = 7 TeV in the lepton+jets final state with the ATLAS detector. (2015) - Lemmer, Boris, 1984-
No abstract available